The connectivity / conversion paradigm - A new approach to the classification of psychosomatic disorders. (January 2019) - Goetzmann, Lutz; Siegel, Adrian; Ruettner, Barbara
Abstract: The classification systems DSM-5 and ICD-10/11 are predominantly based on a phenomenological description of psychic disorders. Psychological and neurobiological findings are only marginally considered. In a conceptual framework, the article proposes a classification system for psychosomatic disorders encompassing descriptive, psychological, and neurobiological aspects. We suggest "connectivity" (neurobiological term)/"conversion" (psychological term) as the common factor which translates emotional distress into physical symptoms. Three types of "conversion disorder" can clinically be distinguished: 1.) The dissociative type comprises a down-regulation of emotionality. 2.) In the asymbolic-operational type, only the physical part of distress is perceived. 3.) The symbolic-expressive type is characterized by the fact that unconscious, mostly conflict-laden images are presented with the aid of symbolic physical symptoms. In a mixed form, the aforementioned conversion types may occur simultaneously or at different times. This multidimensional classification – against the background of the connectivity/conversion paradigm - might become a prerequisite for specific psychotherapeutic interventions tailored to the respective conversion types. Highlights: Psychosomatic classification requires a new approach, encompassing descriptive, psychological and neurobiological aspects. Against the background of the "connectivity/conversion paradigm" psychosomatic disorders may be better understood. Clinically, three subtypes of conversion disorders (dissociative, asymbolic-operational, symbolic-expressive) are proposed.